Genetic variability of Sargassum liebmannii on the coast of Jalisco in the central Mexican Pacific revealed by molecular markers and morphological traits - Hwan Woo Jung-Kim (Elsevier, 2021)
Background: Sargassum liebmannii is widely distributed throughout rocky, coastal upwelling areas in the tropical Mexican Pacific. This brown algae is of great environmental and industrial importance. However, no information is available that documents the genetic or phenotypic variability of the species, which is needed to determine how it may react to environmental variation related to climate change. In this study, S. liebmannii specimens were collected from the coast of Jalisco, Mexico, and molecular and morphological characterization was conducted. Intraspecific variability was estimated according to the study areas. Results: The inter-simple sequence repeat (ISSR) markers indicated a polymorphism percentage of 95%. The Shannon index and Nei index showed relatively low values among the populations (0.3569 and 0.081, respectively). On the other hand, the genetic differentiation coefficient indicated inter- and intrapopulation values of 36.69% and 63.31%, respectively. The Jaccard similarity coefficient was used to determine the degree of similarity among individuals by geographical area. The morphological characteristics and environmental variables that were used to correlate phenotypes and genotypes indicated that S. liebmannii showed low genetic flow because of the presence of geographical barriers due to substrate that was not optimal for algal development. Conclusions: The ISSR markers were useful for detecting genetic differences among S. liebmannii individuals. The results indicate that a coupled genotypic-phenotypic study is beneficial for documenting the variation present in the little-studied algal species. These studies may be used in future research to clarify taxonomic controversies while generating additional genomic information.How to cite: Jung-Kim HW, Hernández-Herrera RM, Enciso-Padilla I, et al. Genetic variability of Sargassum liebmannii on the coast of Jalisco in the central Mexican Pacific revealed by molecular markers and morphological traits. Electron J Biotechnol 2021;54. https://doi.org/10.1016/j.ejbt.2021.08.003